2018
DOI: 10.4314/jasem.v22i9.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ecotoxicological Assessment of Acetaminophen and Diclofenac using Freshwater African Catfish <i>Clarias gariepinus</i> (Burchell 1822)

Abstract: The use and abuse of analgesics, commonly referred to as painkillers is on the rise globally. This study examined the acute toxicity and sub-lethal effects on liver function (ALT, AST, ALP) and anti-oxidative stress enzymes of the African Catfish, Clarias gariepinus, exposed to two analgesics, acetaminophen and diclofenac. The fingerlings (4 weeks old), were exposed to high concentrations of both analgesics to determine their acute toxicity of a 96 h period. The results indicated that diclofenac was approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The concentrations of acetaminophen and diclofenac which are capable of causing acute toxicological effects in some aquatic organisms were much higher than their environmental concentrations. For example, the 96 h LC50 of acetaminophen and diclofenac for juveniles of Clarias gariepinus were 1283.6 mg/L and 2.6 mg/L respectively (Folarin et al, 2018). However, prolonged exposure to these micropollutants at environmental concentrations is capable of chronic biological effects on algae (Osorio et al, 2016) and some biological effects such as oxidative stress in many non-target aquatic organisms (Mehinto et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of acetaminophen and diclofenac which are capable of causing acute toxicological effects in some aquatic organisms were much higher than their environmental concentrations. For example, the 96 h LC50 of acetaminophen and diclofenac for juveniles of Clarias gariepinus were 1283.6 mg/L and 2.6 mg/L respectively (Folarin et al, 2018). However, prolonged exposure to these micropollutants at environmental concentrations is capable of chronic biological effects on algae (Osorio et al, 2016) and some biological effects such as oxidative stress in many non-target aquatic organisms (Mehinto et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The differential responses under T1 and T2 conditions demonstrate the sensitivity of these enzymes to environmental contaminants ( Figure 1 a–d). These enzymes play a critical role in amino acid metabolism, gluconeogenesis, and oxidation, underscoring their importance in fish physiology 31 It is reported that AST activity in the liver was decreased but increased in plasma 32 , 33 explained the decreased AST activity caused due to hepatocytic damage and organ inadequacy. 34 These results align with prior research that has emphasized the influence of AST activity on metabolism, particularly in the liver, and its potential regulatory effects on fish metabolic processes.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important targets of ROS is membrane lipids which undergo peroxidation (LPO). Thus LPO estimation has also been successfully employed to signify oxidative stress induced in aquatic animals by such chemicals [23]. The present study was designed to investigate the acute and sub-lethal effects of a pharmaceutical product diclofenac on the oxidative stress parameters of Tilapia fish (O. niloticus).…”
Section: Introductionmentioning
confidence: 99%